Participatory gesture design: an investigation of user-defined gestures for conducting an informational search using a tablet device - Rakubutu, Tsele (My University, 2014)
Multi-touch technology, used in consumer products such as the iPad, enables users to register multiple points of contact at the same time; this enables a user to interact with a touch screen interface using several fingers on one hand, or even both hands. This affords interface designers the opportunity to define gestural interactions based on what is most natural for users and not on merely what can be recognised and processed by technology. In light of this, the research question that this study aimed to address was: what is the most intuitive user-defined gesture set for conducting an informational search on a multi-touch tablet web browser? In addressing this research question, the aim of this study was to create a user-defined gesture set for conducting an informational search on a multi-touch tablet web browser, based on gestures elicited from participants with little or no experience with touch screen devices. It was necessary to use these participants as users who are familiar with touch screen interfaces would draw upon the gestures they have learnt or used before, and would therefore be biased in the gestures they proposed. Inexperienced or naïve users would simply provide gestures that came naturally to them, providing a more accurate reflection of what a typical, unbiased user would do. A set of hypotheses, relating to the gestures that would be elicited from this participant group, were drawn up and investigated. These investigations yielded the following key findings: • The use of two-handed gestures should be limited. • If two-handed gestures are developed for a specific function, an alternative one-handed gesture should be made available. • It is not be advisable to create completely novel gestures for tablet web browsing that do not correspond to any of the ways in which desktop web browsing is performed. • Should novel gestures be developed for tablet web browsing, gestures that are desktop computing adaptations, including those that require menu access, should be made available as alternatives to users. • Tasks should be designed is such a way that they may be completed with a variety of gestures. • Complex tasks should be designed in such a way that they may be achieved through varying combinations of gestures. These findings may assist interface designers and developers in the gestures they design or developer for their applications. In addition to these findings, the study presents a coherent, user-defined gesture set that may be used in practice by designers or developers.
Keywords: Multi-touch technology; Interface design; Touch screens; Web browsing